Optimizing duration of pharmacotherapy in patients with irritable bowel syndrome: an Indian perspective - Ramesh, G. N.; Pratap, Nitesh (International Journal of Research in Medical Sciences, 2024)
Irritable bowel syndrome (IBS) is the most common gut-brain disorder with a rising prevalence globally, including in India. IBS places a major financial and health burden on patients, making a proper diagnosis and course of treatment crucial for enhancing quality of life. The frequent occurrence of anxiety and depression in patients with IBS requires the treatment of both gastrointestinal and psychological symptoms of the condition with antispasmodics and anxiolytics. This review discusses the epidemiological, diagnostic, and pathophysiological features of IBS and the numerous treatment regimens that are utilized, as well as the perspectives of specialists in the area addressing the difficulties and ideal management techniques. The role of combination treatments along with emphasis on associated psychological and psychiatric comorbidities in Indian patients has been evaluated. The experts reviewed the ideal duration of antispasmodic medication and various guideline recommendations on length of treatment to avoid recurrence while keeping in mind the chronic and recurring character of IBS. An appropriate diagnostic strategy and effective treatment protocol and duration can help in the long-term management of IBS.